PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VB SDN 023 SEDINGINAN - ', Ranowiradi; Alpusari, Mahmud; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Background problem in this research is the result of the low grade science students learn VB SD Negeri 023 Sedinginan with an average value of 65, out of 18 students have not reached the KKM as many as 11 people (61.11%) while achieving KKM only 7 people (38, 89%). Rumusam problem in this research is the application of  Inquiry learning model can improve learning outcomes VB grade science students of SD Negeri 023 Sedinginan? The purpose of this study to improve student learning outcomes through the implementation of IPA Inquiry learning model in the class VB 023 Sedinginan Elementary School. Research was conducted in the second semester (2) in the academic year 2015/2016 in March and May 2016. The subjects were students of class VB 023 Sedinginan Elementary School the number of students 18 students terdidri of 9 male and 9 female students. Design of this research is the Classroom Action Research (PTK). The study was conducted role in two cycles, ie four meetings twice daily test material. Data collection instruments on recearh are observation sheets teachers and students as well as the achievement test. Once applied, the Inquiry learning model results showed that the activity of teachers increased by 70.5% from the first cycle to 89.59% in the second cycle, the student activity increased by 66.67% from the first cycle to 87.5 % in cyclically II. Learning outcomes of students has increased from a base score denagan average 65 rose to 69.17 in the first cycle UH, UH then in the second cycle students' average score increased to 82.5 at UH II. The completeness classically increased from 38.89% to preliminary date increased to 50% in the first cycle, subsequently increased to 83.33% in the second cycle. Based on these results it can be concluded that the application of Inquiry learning model can improve learning outcomes VB grade science students of SD State 023 Sedinginan. Key Word : Guided Inguiry Learning Model